The Properties of Humic Acids Extracted from Four Sources of Organic Matters and Their Ability to Bind Fe2+ at New Established Rice Field - Herviyanti, .; Prasetyo, Teguh Budi; Ahmad, Fachri; Darmawan, . (JOURNAL OF TROPICAL SOILS, 2010)
The Properties of Humic Acids Extracted from Four Sources of Organic Matters and Their Ability to Bind Fe2+ at New Established Rice Field (Herviyanti, TB Prasetyo, F Ahmad and Darmawan):  In order to identify the properties of humic acid extracted from four kinds of organic matters (a peat soil, a stable manure, a compost of rice straw and a municipal waste)  and their potentiality to bind Fe2+  at new established rice field, a series of experiment was done in Soil Laboratory Faculty of Agriculture, Andalas University Padang. First step was characterization of functional groups and other chemical properties of humic acids, and their reaction with Fe2+. The second step was to examine the ability of humic acids to bind Fe2+ solution at new established rice field by conducting incubation experiments.  The experiment used  a completely randomized design with three replications.  The 450 ppm Fe solution was treated with 0, 50, 100, 150, 200, 250, 300, 350, 400, and 450 ppm humic acids and incubated for 24 hours.  While top soil samples taken from Sitiung, West Sumatera were treated with 0,100, 200, 300, and 400 ppm humic acids, flooded with deionized water, and incubated for 6 weeks.  The result showed that   the functional group and other chemical characteristic of humic acid from rice straw compost and peat soil were better than those of manure and municipal waste compost. Functional group of both humic acids was dominated by COO-. High reactivity of the humic acid had been found when humic acids were added to Fe solution with ratio 1 : 1. Use of humic acid extracted from peat soil with the levels from 0 to 100, 200, 300, and 400 ppm decreased the Fe2+ concentration from 1.361 ppm to  910, 860, 831, and 776 ppm, respectively at new established rice field.  While the use of humic acid extracted from  rice straw compost with the same levels as above decreased the Fe2+ concentration  from 1361 to 770, 701, 612, and 600 ppm, respectively, after four weeks of flooding.